HUMAN RESOURCE MANAGEMENTSTRATEGIES FOR MANAGING THEAGINGWORKFORCE IN INDIAN HOSPITALITYFIRMS - CHAND, MOHINDER (ITB Journal Publisher, LPPM ITB, 2009)
This paper examines the critical issues relating to the management of aging workforce in the Indian hospitality firms. It is based on an e-mail survey of 250 hospitality firms, supplemented by 28 indepth interviews with HR manager- owners located in the northern India. The results indicated that a number of different HRM strategies are important for the efficient use of aging workforce in Indian hospitality firms related to the work-life balance and flexible work practices ,workforce planning, Career planning & development, retirement & pensions, knowledge management, training & development and so forth. These findings suggest that HRM strategies might be crucial to the management of aging workforce in the Indian hospitality firms.